2020
DOI: 10.20944/preprints202004.0308.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Normalized Mortality Rate Showed the Diverse Severity of COVID-19 and Its Association With Other Chronic Diseases

Abstract: Covid-19 has given a halt to all the activities in the world. Europe was most affected, followed by the United States of America. It has taken more than 225,000 lives until now. In this study, we have assessed the severity of Covid-19 by analyzing the mortality rate of Covid-19 and other chronic diseases. The Covid-19 data and “death rate” data caused by other diseases were downloaded from the world health organization (WHO) website. A normalized method was used to see the mortality rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The study carried out in Finland have evidently shown that prevention can certainly control the infection to a extend in people being overweight and suffering from glucose metabolism [33]. It also revealed that higher threat among diabetic people could able to reduce upto 58% with their daily physical activity and by proper managing their diet.…”
Section: In Europementioning
confidence: 99%
“…The study carried out in Finland have evidently shown that prevention can certainly control the infection to a extend in people being overweight and suffering from glucose metabolism [33]. It also revealed that higher threat among diabetic people could able to reduce upto 58% with their daily physical activity and by proper managing their diet.…”
Section: In Europementioning
confidence: 99%